Helping Your Teenager Discover Spirituality - Larry Forthun; Angelica Shaw (EDIS, 2018)
Many life transitions and transformations occur during the teen years (ages 11-19). Bodies mature, thinking ability improves, and teens learn to manage many new emotions. Teens are striving to “find themselves” and to answer the question, “Who am I?” The answers to such questions often include a spiritual search for meaning and purpose in life. This 2-page fact sheet is a minor revision written by Larry Forthun and Angelica Johns, and published by the UF Department of Family, Youth and Community Sciences, January 2018.